Study of Electricity Utilization in Beach Resort Hotel, Chonburi Province for Energy Conservation - Nattabhas Rasmimanonda; Suphawadee Ratanamart (My University, 2015)
This research investigated the standard electricity utilization in beach resort hotels based on a survey of four 4-star beach resort hotels in Chonburi, Thailand conducted in 2014. The main objective of the project was to know proportion of electricity in end-use category. Each hotel has total usable areas of 34,878.50, 24,706.56, 17,533.40 and 10,910.56 m2 with total air-conditioned areas of 17,364.45, 8,327.48, 5368.35 and 8,212.56 m2 respectively. The results showed that the hotel with most usable areas, air-conditioned space and using central air conditioning system has the minimum index value of electricity utilization for air conditioning system by compared with electrical consumption for air conditioning system per air-conditioned area equal to 72.36 kWh/m2/year. Unlike other three hotels with using split type air conditioning system that have this value equal to 89.92, 103.67 and 136.21 kWh/m2/year. Every hotel has the lowest proportion of electricity in lighting system compared with electrical consumption of air conditioning system and electric-mechanical system, which accounted for 5 – 10% of total electricity utilization and the maximum value of lighting density power is lower than 12 W/m2, which is considered the standard of Thailand Energy Conservation Promotion Act. Moreover, the study also found that the hotel with usable area most has annual electricity consumption for electric-mechanical equipment system that most in refrigerators, followed by pumps and other kitchen equipment, respectively which accounted for 53% of total electricity utilization. Finally, the results can also use as guidelines for designing beach resort hotels, Chonburi province for energy conservation, including the use of air conditioning systems appropriately.
Keywords: USable; Building Energy and Comfort Optimization